Three dimensional fluorescent spectroscopy analysis for the evaluation of organic matter removal from industrial estate wastewater by stabilization ponds - C. Musikavong (2018)
The fluorescent excitation emission matrix (FEEM) was utilized to evaluate the removal of organic matter by stabilization ponds, which consist of aeration, facultative, and oxidation ponds of a central wastewater treatment plant of an industrial estate in northern Thailand. The result shows that six fluorescent peaks of influent wastewater and effluent water after aeration, facultative, and oxidation ponds were detected from the FEEMs at 230 nmEx/295 nmEm (A), 275 nmEx/300 nmEm (B), 240 nmEx/355 nmEm (C), 280 nmEx/355 nmEm (D), 275 nmEx/410 nmEm (E) and 330 nmEx/410 nmEm (F). The putative origins of peaks A and B, C and D, and E and F were tyrosine-like, tryptophan-like, and humic and fulvic acid-like substances, respectively. The aeration pond was the main course of action used to reduce the tyrosine-like substances at peaks A and B by 88 and 52%, respectively, and tryptophan-like substances at peaks C and D by 43 and 39%, respectively. There was only a 20 per cent decrease of humic and fulvic acid-like substances at peak E and an 18 per cent decrease at peak F through the use of aeration ponds. Total per cent reductions of total fluorescent organic matter after aeration ponds; facultative ponds; and oxidation ponds were 46, 51 and 54%, respectively. These values were notably similar to the total percent reduction of DOC by the same respective processes at 54, 53, and 55%. © IWA Publishing 2007.